ASIC1A in neurons is critical for fear‐related behaviors. (21st July 2017) - Taugher, R. J.; Lu, Y.; Fan, R.; Ghobbeh, A.; Kreple, C. J.; Faraci, F. M.; Wemmie, J. A.
Abstract : Acid‐sensing ion channels (ASICs) have been implicated in fear‐, addiction‐ and depression‐related behaviors in mice. While these effects have been attributed to ASIC1A in neurons, it has been reported that ASICs may also function in nonneuronal cells. To determine if ASIC1A in neurons is indeed required, we generated neuron‐specific knockout (KO) mice with floxed Asic1a alleles disrupted by Cre recombinase driven by the neuron‐specific synapsin I promoter ( SynAsic1a KO mice ). We confirmed that Cre expression occurred in neurons, but not all neurons, and not in nonneuronal cells including astrocytes. Consequent loss of ASIC1A in some but not all neurons was verified by western blotting, immunohistochemistry and electrophysiology. We found ASIC1A was disrupted in fear circuit neurons, and SynAsic1a KO mice exhibited prominent deficits in multiple fear‐related behaviors including Pavlovian fear conditioning to cue and context, predator odor‐evoked freezing and freezing responses to carbon dioxide inhalation. In contrast, in the nucleus accumbens ASIC1A expression was relatively normal in SynAsic1a KO mice, and consistent with this observation, cocaine conditioned place preference (CPP) was normal. Interestingly, depression‐related behavior in the forced swim test, which has been previously linked to ASIC1A in the amygdala, was also normal. Together, these data suggest neurons are an important site of ASIC1A action in fear‐related behaviors, whereas other behaviors likely depend on ASIC1A in other neurons or cell types not targeted in SynAsic1a KO mice. These findings highlight the need for further work to discern the roles of ASICs in specific cell types and brain sites. Abstract : Mice with neuron‐specific disruption of acid‐sensing ion channel 1A (ASIC1A) freeze less in fear conditioning, 10% CO2 and predator odor (trimethylthiazoline) assays.